Practices related to sharps disposal among diabetic patients in Sri Lanka - Atukorala, K. R. (Asia Pac Fam Med, 2018)
BACKGROUND: Patients with diabetes on insulin therapy use sharps (e.g., needles) on a regular basis and a considerable proportion of them, within their home environments. These sharps and other bloodstained materials, if not disposed of appropriately has the potential to be a public health hazard. OBJECTIVE: Our objective was to explore the practices related to sharps disposal among patients with diabetes from North Colombo Teaching Hospital (CNTH), Ragama, Sri Lanka. METHODS: We conducted a cross-sectional study on 158 patients with diabetes from the CNTH. Patients had to use sharps for the daily management of their disease for inclusion into the study group. Data were collected on sharps disposal practices using an interviewer-administered questionnaire. Clinic records were also used as a secondary data source. RESULTS: Most patients, 153/158 (96.8%) used syringes to inject insulin. Forty-three patients (27%) involved others (e.g., family) when disposing of sharps. Used sharps were commonly disposed to the household garbage bin by 66 participants (41.7%). Other methods used for sharps disposal were: sharps container, toilet pit, household garbage dump and indiscriminate measures. Importantly most patients, 147 (93%) had received no information on how to dispose of sharps after usage. CONCLUSION: Patients commonly used unsafe practices in home-based sharps disposal. These included disposing of in the household garbage bin, burning sharps in the household garbage dump and disposing of into the common garbage dump of the community. Being male and being > 60 years of age was associated with a higher dependence on family members for sharps disposal. Patient education and public resources for sharps handling can help improve this situation.